Effect of Exam-Focused and Teacher-Centered Education Systems on Students' Cognitive and Psychological Competencies - Ghaleb, Belal Dahiam Saif (International Journal of Multidisciplinary Approach Research and Science, 2024)
This Paper undertakes a thorough analysis of how students' cognitive and psychological competencies are influenced by education systems that prioritize exams and center teaching around instructors. Analyzes the limitations of traditional models and suggests alternative approaches to improve the learning experience by examining the literature as a research method and drawing on various scientific references. The teacher-centered educational model, characterized by rote learning and standardized testing. It has been examined for its potential to inhibit critical thinking and creativity. Psychologically, the study investigates in depth the work of Madigan, Curran, and Lonsdale (2016) and Carol Dweck (2006) to highlight the stress and fixed mindset associated with high-stakes exams. The pressures created by exam-oriented systems are explored, shedding light on the potential damage to teacher-student relationships and the overall quality of education. Additionally, the weaknesses of exam-oriented education, such as student-centeredness and lack of practical applications, are discussed. The article emphasizes the necessity of moving towards student-centered models that take individual differences into account, encourage active participation, and prioritize holistic development. To solve these problems, various solutions are proposed in the article. Cognitively, the article underscores the importance of balancing test preparation with student-centered learning. The article promotes a reimagined pedagogical strategy that emphasizes the all-encompassing growth of students, equipping them not just for examinations but also for the intricacies of life outside traditional academic settings. The extensive references cited contribute to a well-rounded comprehension of the intricacies and potential remedies linked to education systems focused on exams and centered around teachers.